Efficacy of routine second-look endoscopy after endoscopic hemostasis in patients with acute peptic ulcer bleeding: systematic review and meta-analysis - Benites-Goñi, H (2024)
OBJECTIVE: To evaluate the efficacy of scheduled second-look endoscopy in patients with acute peptic ulcer bleeding (PUB). MATERIALS AND METHODS: We systematically search in four databases for randomized controlled trials (RCTs) that evaluated the usefulness of scheduled second-look endoscopy vs. single endoscopy in patients with PUB. Our primary outcome was rebleeding. Secondary outcomes were surgery, mortality, and the number of units of blood transfused (NUBT). All meta-analyses were performed using a random-effects model. Pooled risk ratio (RR) and mean difference (MD), with their 95% confidence intervals (CIs) were calculated for categorical and continuous outcomes, respectively. The risk of bias was assessed using the Cochrane RoB 2.0 tool, and the quality of evidence (QoE) was rated with the GRADE approach. RESULTS: Eight full-text RCTs and two RCT abstracts were included (n=1513). We did not find differences in rebleeding (RR, 0.78; 95% CI, 0.53-1.14, moderate QoE), surgery (RR, 0.58; 95% CI, 0.29-1.15, moderate QoE), mortality (RR, 0.89; 95% CI, 0.46-1.71, moderate QoE) or NUBT (MD, -0.01 units; 95% CI, -0.3 to 0.28, low QoE) between second-look and single endoscopy. Sensitivity analyses had similar results to the main analyses. CONCLUSIONS: Routine second-look endoscopy was not more efficacious than single endoscopy in patients with PUB.